Dental phenotypic shape variation supports a multiple dispersal model for anatomically modern humans in Southeast Asia. Issue 112 (November 2017) - Corny, Julien; Galland, Manon; Arzarello, Marta; Bacon, Anne-Marie; Demeter, Fabrice; Grimaud-Hervé, Dominique; Higham, Charles; Matsumura, Hirofumi; Nguyen, Lan Cuong; Nguyen, Thi Kim Thuy; Nguyen, Viet; Oxenham, Marc; et al.
Abstract: The population history of anatomically modern humans (AMH) in Southeast Asia (SEA) is a highly debated topic. The impact of sea level variations related to the Last Glacial Maximum (LGM) and the Neolithic diffusion on past population dispersals are two key issues. We have investigated competing AMH dispersal hypotheses in SEA through the analysis of dental phenotype shape variation on the basis of very large archaeological samples employing two complementary approaches. We first explored the structure of between- and within-group shape variation of permanent human molar crowns. Second, we undertook a direct test of competing hypotheses through a modeling approach. Our results identify a significant LGM-mediated AMH expansion and a strong biological impact of the spread of Neolithic farmers into SEA during the Holocene. The present work thus favors a "multiple AMH dispersal" hypothesis for the population history of SEA, reconciling phenotypic and recent genomic data.